Il tempio nel tempio Il monumento ligneo a Rousseau nel Panthéon di Parigi, dalla capanna vitruviana ai Lumi francesi - Guzzo, Eleonora (Premio Tesi di Dottorato, 2015)
The wooden monument in the Panthéon in Paris unfolds its originality in conforming itself as a real small-scale rustic temple. Its formal features recall, on the one hand, the archetypal origin of western architecture, through adherence to the literary topos of the Vitruvian hut, on the other hand the return to simple natural principles preached by Rousseau. The tombeau project is considered both in its prestigious theoretical context and in the historical context of revolutionary France. The analysis of unpublished documents, the elaboration of new surveys and digital photographic studies support the attribution hypotheses, just as they complete the examination of the classic proportions of the work, between rule and revolution.